Critical success factors for embedding carbon management in organizations: lessons from the UK higher education sector. Issue 5 (2nd November 2017) - Mazhar, Muhammad Usman; Bull, Richard; Lemon, Mark
ABSTRACT: Organizations are under increasing pressure from governments and stakeholders to reduce carbon emissions from their business operations for climate change mitigation. Universities are not exempt from this challenge and are operating in a complex external environment, not least responding to the UK government's Climate Change Act 2008 (80% carbon reductions by 2050 as per 1990 baseline). In 2012–2013, the UK Higher Education (HE) sector consumed 7.9 billion kWh of energy and produced 2.3 million tonnes of carbon emissions. This indicates the scale of the challenge and carbon management is central to reduce carbon emissions. However, effective processes for implementing and embedding carbon management in organizations in general, and universities in particular, have yet to be realized. This paper explores the critical success factors (CSFs) for embedding carbon management in universities and, more widely, in organizations. This exploratory study adopted a mixed-methods approach including the content analysis of universities' carbon management plans alongside semi-structured interviews in the UK HE sector. The paper identifies six key factors for successfully embedding carbon management that are pertinent not just for the HE sector, but to organizations broadly: senior management leadership; funding and resources; stakeholder engagement; planning; governance and management; and evaluation and reporting.